Polish State Railways as a Mode of Transport for Troops of the Warsaw Pact Technology in Service of a Doctrine - Tucholski, Zbigniew (Geschichte - Erinnerung - Politik. Studies in History, Memory and Politics, 2020)
The subject of the book is the history of the planned use of Polish railway infrastructure during the Cold War as part of the strategic plans of the Warsaw Pact. Analysing both technical and operational issues related to railway military transportation in a historical perspective, the author presents the history of the military transportation service of the Polish Army and provides a detailed characteristics of the organizational structure, equipment and tasks of the military transportation units and railway troops. The book also deals with rail transports of the Soviet Army on the Polish State Railways. The work is not only the result of archival queries and interviews with retired officers of the military transportation service but also field research of railway infrastructure.